A human rights analysis of the education of children with visual impairments in The Gambia-Lessons from Kenya - Murungi, Nkatha (University of Pretoria, 2025)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2025.